Skin delivery of nisoldipine from niosome proconcentrate - Gamal M. El Maghraby, Amal A. Ahmed, Mohamed A. Osman (Journal of Applied Pharmaceutical Science, 2014)
Nisoldipine is used for treatment of hypertension and angina pectoris. However, it suffers from very low bioavailability due to its extensive pre-systemic metabolism. This together with its low dose made it excellent candidate for transdermal delivery. Accordingly, the aim of this study was to develop and evaluate transdermal delivery system for optimization of nisoldipine skin permeability. Proniosomes comprising cholesterol and span 60 with different ratios together with ethanol and minimal water were evaluated for such aim. The developed formulations were assessed with respect to drug entrapment efficiency, viscosity, in vitro drug release and transdermal permeability. All proniosomal formulations have significantly enhanced transdermal delivery of nisoldipine compared with saturated aqueous solution of the drug. Increasing cholesterol content resulted in reduced drug flux. The study was extended to compare the efficacy of such proniosomes to the corresponding niosomes. Proniosomes significantly optimized transdermal delivery of nisoldipine compared to their hydrated form. Such results contradict the hypothesis which claimed the necessity for niosome formation from proniosomes for efficient transdermal delivery with penetration enhancement being mainly responsible for improved delivery.
Keywords: Nisoldipine, Proniosomes, Niosomes,Skin delivery, Cholesterol.